Academic Librarians’ Student Engagement for Promoting Information Literacy and Artificial Intelligence Instruction in Nigerian Tertiary Institutions - Kayode Sunday John Dada (Qualitative and Quantitative Research Center, 2026)
As artificial intelligence (AI) platforms transform higher education, reshaping the instructional role of academic libraries has become critical. This study empirically examined the nature and effectiveness of academic librarians' student engagement strategies for promoting information literacy (IL) and AI instruction in Nigerian tertiary institutions. Anchored on the ACRL Framework for Information Literacy for Higher Education and the Technology Acceptance Model (TAM), the study adopted a cross-sectional survey design. A total of 412 academic librarians drawn from 38 federal and state universities, polytechnics, and colleges of education in Nigeria participated through a structured questionnaire. Data were analysed using descriptive and inferential statistics. Findings revealed that in-person reference consultations and formal library instruction sessions were the dominant modes of student engagement. Academic librarians reported moderate-to-high competence in IL instruction but comparatively lower confidence in delivering AI literacy content. Regression analysis showed that engagement frequency (β = 0.41, p < 0.001), perceived administrative support (β = 0.29, p < 0.01), and prior AI training (β = 0.33, p < 0.001) significantly predicted the effectiveness of AI instruction. Significant barriers included inadequate digital infrastructure, absence of formal AI curricula, and limited professional development. The study recommends institutionalising AI literacy within higher education library frameworks, implementing structured professional development, and driving policy reforms that embed IL and AI instruction into national library standards for Nigerian tertiary education.